2017
DOI: 10.1038/srep40164
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the modes of action for bioactive compounds in a cell-specific manner by large-scale chemically-induced transcriptomics

Abstract: The identification of the modes of action of bioactive compounds is a major challenge in chemical systems biology of diseases. Genome-wide expression profiling of transcriptional responses to compound treatment for human cell lines is a promising unbiased approach for the mode-of-action analysis. Here we developed a novel approach to elucidate the modes of action of bioactive compounds in a cell-specific manner using large-scale chemically-induced transcriptome data acquired from the Library of Integrated Netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 50 publications
0
50
0
Order By: Relevance
“…In the context of toxicogenomics, use of low-cost, high-throughput transcriptomic technologies (Bush, et al, 2017;Bushel, et al, 2018;Subramanian, et al, 2017), combined with pasLINCS analysis may open alternative avenues for high throughput safety evaluation of commercial chemicals, pesticides, food additives/contaminants, and medical products (Kavlock, et al, 2009;Kleinstreuer, et al, 2014). Previous studies have established the potential of assigning MOA of a chemical perturbagen based on comparison of their transcriptional signatures to the signatures of chemicals with known MOA (Iwata, et al, 2017;Subramanian, et al, 2017;Wang, et al, 2018). For example, the preciously derived PI3K inhibitor signature constructed from TSes of known chemical inhibitors (Zhang, et al, 2017) showed similar level of association with L1000 mTOR pathway inhibitors as we observed with our PAS (Fig 2D).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of toxicogenomics, use of low-cost, high-throughput transcriptomic technologies (Bush, et al, 2017;Bushel, et al, 2018;Subramanian, et al, 2017), combined with pasLINCS analysis may open alternative avenues for high throughput safety evaluation of commercial chemicals, pesticides, food additives/contaminants, and medical products (Kavlock, et al, 2009;Kleinstreuer, et al, 2014). Previous studies have established the potential of assigning MOA of a chemical perturbagen based on comparison of their transcriptional signatures to the signatures of chemicals with known MOA (Iwata, et al, 2017;Subramanian, et al, 2017;Wang, et al, 2018). For example, the preciously derived PI3K inhibitor signature constructed from TSes of known chemical inhibitors (Zhang, et al, 2017) showed similar level of association with L1000 mTOR pathway inhibitors as we observed with our PAS (Fig 2D).…”
Section: Discussionmentioning
confidence: 99%
“…The main idea underlying several current methods, including in silico DR, is to identify genes whose expression levels are inversely correlated in the context of disease and drug treatment . These three approaches represent alternative and complementary approaches to the discovery of repositioned drugs.…”
Section: Approach For Drug Repositioningmentioning
confidence: 99%
“…While there are numerous studies using LINCS data to investigate the mechanism-of-action (MOA) of drugs and to promote clinical translation of MOA information (Iwata et al, 2017;Lamb et al, 2006;Pabon et al, 2018;Siavelis et al, 2015;Subramanian et al, 2017;Wang et al, 2016), few studies aim to use the data to learn to represent the cellular signaling system as an information encoder and examine how different perturbagens affect the system. It can be imagined that perturbing different signaling components at different levels of a signaling cascade would lead to compositional statistical structure in the data.…”
Section: Introductionmentioning
confidence: 99%